Molecular epidemiology of anaplasmosis in small ruminants along a human-livestock-wildlife interface in Uganda - Keneth Iceland, Kasozi; Simon Peter, Musinguzi (Elsevier Ltd, 2021)
Background: Information as regards the epidemiology of the Anaplasmataceae in small ruminants in several lowand middle-income countries is scarce. Methods: In this study a total of 712 DNA samples collected from small ruminants were analyzed for Anaplasmataceae and Anaplasma ovis using the 16S rRNA and MSP4 genes respectively. Infection risk was assessed by location, sex and age of the animals and qGIS® was used to construct spatial maps. Results: The prevalence of Anaplasmataceae spp was 89.1% (95% CI: 77.5–95.9) and 79.1% (95% CI: 75.9–82.1) in ovines and caprines respectively (RR ¼ 1.1, 95% CI: 1.0–1.3); higher than those previously reported in other eastern African countries. The prevalence of A. ovis was 26.1% and 25.4% for both ovines and caprines respectively with ovines showing significantly higher levels of infection than caprines (P < 0.05). The risk of Anaplasma ovis infections was not affected by age (OR ¼ 1.2, 95% CI: 0.9–1.7) or sex (OR ¼ 1.1, 95% CI: 0.6–2.0). Small ruminants located at the forest edge (<0.3 km) showed higher A. ovis prevalence than those found inland with infections present in the midland regions associated with increased agricultural activity. Conclusion: Anaplasma ovis remains a major challenge for small ruminant husbandry in Uganda and infections are under-reported. Policy efforts to prioritize management of Anaplasmataceae for small ruminant health would promote livestock productivity in vulnerable communities, improving livelihoods and ecosystem health.